FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN MAKANAN PENDAMPING ASI DINI - Sri Yulianti Kumalasari; Febriana ' Sabrian; Oswati Hasanah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this study was to identify factors associated with early complementary feeding in infants. This was a descriptive correlative study with cross sectional design.This research was conducted in the working area of Sidomulyo Public Health Center Pekanbaru involving 92 respondents. The sampling method was purposive sample. Measuring instrument used was a questionnaire that has been tested for validity and reliability. The analysis used univariate and bivariate analysis. The results showed that there is a relationship between knowledge (p value = 0.024), activity (p value = 0.005), income (value = 0.022) and health workers recommendation (p value = 0.037) with early complementary feeding, but there is no relationship between the myth (p value = 0.141) with early complementary feeding. The results of this study recommends community health centers to be active to provide health education programs for the prevention of early complementary feeding practice in the working area of Sidomulyo Public Health Center. Keywords: factors, early complementary feeding, infants